Parametric study of lightweight wooden wall assemblies for cold and subarctic climates using external insulation - Gosselin, Louis; Blanchet, Pierre; Caron-Rousseau, Alexis (Buildings, 2022)
While externally insulated wall assemblies are widely recognized for their hygrothermal performance, few research projects have focused on the impact of shifting the entire wall insulation to the exterior side of a structural cavity in cold or subarctic climates or its effectiveness in terms of acoustic performance and airtightness. The objective of this study was to propose fully externally insulated assemblies that could be used in cold and subarctic climates by assessing the benefits of the hygrothermal performance of these assemblies and by achieving a comparable airtightness and sound transmission performance to the modern assemblies that are currently built in North America. The results suggested that the externally insulated assemblies limited the risk of condensation occurring inside structural cavities and allowed for faster drying than the modern assemblies when exposed to water infiltration or high water contents in all climates that were tested. The assemblies with external airtight insulation boards were more airtight than assemblies with air barrier membranes and, in addition, assemblies with external soundproof insulation were shown to be necessary to achieve a comparable sound transmission loss to that of a modern assembly.